SWIMMERS REACTION SPEED ON THE START OF 50M FREESTYLE EVENT - Goran Dimitrić; Nebojša Čokorilo; Miroslav Petrović; Milica Bogdanovski; Igor Glavičić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Swimming belongs to the group of monostructural activities as cyclic type with acyclic strucutre at start, turn and finish. Swimming perfomance duting the race can be divided in four main parts: start, turn, swimming and finish. Swimming perfomance analysis is an integral part of swimming competitions (Hay et al., 1983). The aim of this paper if there are gender differences in reaction speed in 50m freestyle. Reaction times of 50 male and 50 female swimmers, participants on European swimming championships - Rome 2009, Italy, were analysed. Based on adequate statistical methods and analysis of results, certain conclusions will be derived.